2017
DOI: 10.4103/jrpp.jrpp_17_30
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of low dose and conventional dose of oral isotretinoin in treatment of moderate and severe acne vulgaris

Abstract: Objective:This study was conducted to compare the effect of low-dose isotretinoin with its conventional dose in patients with moderate and severe acne.Methods:This was a clinical trial conducted on 60 male and female patients with moderate and severe acne vulgaris. The patients were divided into two treatment groups: 0.5 mg/kg/day isotretinoin capsule and low-dose isotretinoin capsule (0.25 mg/kg/day). Patients in both groups received 6-month treatment. At the end of the 6th month and 12th month (6 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…[78] Topical therapies including antibiotics, benzoyl peroxide (BPO), retinoids, and sulfone agents are the first-line treatment in mild to moderate acne. [91011] The most common approach for treating AV is oral antibiotics plus topical retinoid or BPO. BPO is a non antibiotic, anti bacterial agent and lipophilic nature that reduce the sebaceous gland activity.…”
Section: Introductionmentioning
confidence: 99%
“…[78] Topical therapies including antibiotics, benzoyl peroxide (BPO), retinoids, and sulfone agents are the first-line treatment in mild to moderate acne. [91011] The most common approach for treating AV is oral antibiotics plus topical retinoid or BPO. BPO is a non antibiotic, anti bacterial agent and lipophilic nature that reduce the sebaceous gland activity.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies 30,34,36,37,43 demonstrated no statistical difference in clinical efficacy between the low dose versus conventional dose at the end of the treatment period (24-30 weeks), with a similar number and timing of relapses in each group.…”
Section: Low Dose Versus Conventional Regimensmentioning
confidence: 95%
“…One study 30 compared low (0.25 mg/kg/day) versus conventional (0.5 mg/kg/day) dose (alongside a 2‐week regimen of azithromycin and 1 week of prednisolone), demonstrating nonsignificant improvement of acne severity in all groups.…”
Section: Isotretinoin Dosing Regimensmentioning
confidence: 99%
“…G. Faghihi и соавт. [30] провели исследование на 60 больных акне средней и тя желой формы по оценке эффективности стандартной (0,5 мг/кг/cут) и низкодозовой (0,25 мг/кг/сут) терапии СИ в течение 6 мес. Клинических различий между группами не выявили.…”
Section: изотретиноин в дерматологииunclassified